2022
DOI: 10.1111/jan.15361
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of work engagement in frontline supporting nurses during COVID‐19 pandemic: A latent profile analysis

Abstract: Aim The aim was to examine the subgroups of work engagement in frontline nurses during the COVID‐19 pandemic. Background The pandemic may affect the work engagement of nurses who have direct contact with infected patients and lead to a poor quality of care. Identifying classification features of work engagement and tailoring interventions to support frontline nurses is imperative. Design This study utilized a cross‐sectional study design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
4
11
0
Order By: Relevance
“…Work immersion was negatively related to perceived stress, and this relationship has been previously established [34,35] . The study also employed latent pro le analysis to identify heterogeneity in the work immersion of nurses and found results for four latent subgroups, which is consistent with Yin et al [75] and supports the second hypothesis. Our study showed that more than 50% of nurses were in the low or moderately low work immersion group.…”
Section: Discussionsupporting
confidence: 86%
“…Work immersion was negatively related to perceived stress, and this relationship has been previously established [34,35] . The study also employed latent pro le analysis to identify heterogeneity in the work immersion of nurses and found results for four latent subgroups, which is consistent with Yin et al [75] and supports the second hypothesis. Our study showed that more than 50% of nurses were in the low or moderately low work immersion group.…”
Section: Discussionsupporting
confidence: 86%
“…Patients were excluded if they had (i) psychiatric disorders, confusion or severe cognitive impairment, (ii) accompanied by severe organ damage or having malignant tumours. Based on previous studies (Kline, 2015;Park et al, 2022;Yin et al, 2022), we argue that LPA would have reliable statistical results when the sample size reaches 300. Therefore, 400 questionnaires were distributed.…”
Section: Participantsmentioning
confidence: 83%
“…Latent profile analysis (LPA), a method to detect latent sub‐populations within a population from observed data (Spurk et al, 2020), has recently been featured in JAN publications. Choi et al (2022) used LPA to detect profiles of second victim symptoms among nurses, and Yin et al (2022) used it to identify subtypes of work engagement in frontline supporting nurses during the COVID‐19 pandemic. Counterfactual medial analysis (Bulfone et al, 2022) and actor–partner interdependence model (Yuliana et al, 2023), both recently published in JAN , are nuanced methods necessary to understanding how variables may relate and interact through indirect and previously underexplored pathways.…”
Section: Emerging Quantitative Methods In Janmentioning
confidence: 99%